Taxonomy of the genus Ptomaphaginus Portevin (Coleoptera: Leiodidae: Cholevinae: Ptomaphagini) from China, with description of eleven new species - Wang, Cheng-Bin; Zhou, Hong-Zhang (Zootaxa, 2015)
Ptomaphaginus Portevin, 1914 is one of the most speciose genera in the tribe Ptomaphagini (Coleoptera: Leiodidae: Cholevinae). Its members are mainly soil dwellers and are almost all distributed in the Oriental Region. This paper reports eleven new species from China: P. guangxiensis sp. nov. (type locality: Napo, Guangxi autonomous region), P. gutianshanicus sp. nov. (type locality: Gutianshan, Zhejiang province), P. luoi sp. nov. (type locality: Shennongjia, Hubei province), P. newtoni sp. nov. (type locality: Wuzhishan, Hainan province), P. perreaui sp. nov. (type locality: Jinghong, Yunnan province), P. quadricalcarus sp. nov. (type locality: Xishuangbanna, Yunnan province), P. ruzickai sp. nov. (type locality: Baoxing, Sichuan province), P. shennongensis sp. nov. (type locality: Shennongjia, Hubei province), P. wenboi sp. nov. (type locality: Fushan, Taiwan province), P. wuzhishanicus sp. nov. (type locality: Wuzhishan, Hainan province) and P. yui sp. nov. (type locality: Lijiang, Yunnan province). Five other species known to occur in China were also reviewed and mostly redescribed to update the knowledge on their identification. The Chinese fauna of the genus Ptomaphaginus is thus increased to sixteen species. Important characters on the last two visible ventrites and aedeagus in the male as well as on the ventral side of the proleg are discussed, detailed line drawings are offered for each species, and a key to species from China is presented.